The Chase : Fox and O$1 (BHare #2 /s - Evanovich, Janet; Goldberg, Lee, 1962-; Brick, Scott (New York, New York : Random House Audio, 2014)
FBI agent Kate O'Hare must once again covertly team up with brilliant con man Nicholas Fox to take down Carter Grove, a former White House chief of staff who has stolen a rare Chinese artifact from the Smithsonian.
Title from container.
Read by Scott Brick.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Swindlers and swindling -- Fiction; Undercover operations -- Fiction; Theft from museums -- Fiction; Romantic suspense fiction; Audiobooks